The influence of the angle of the trunk flexion and extension in the sagittal plane and flexion in the frontal plane on the value of features describing the spine and pelvis among 7 to 15-year-old youth of both sexes - Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2023)
The aim of the study was to demonstrate the significant effect of the value of the angle of trunk flexion and extension in the sagittal plane and the flexion to the left and right in the frontal plane on the value of selected features describing the spine. Material and methodology. The research was conducted in a group of 2,361 people aged 7 to 15, in 6 semi-annual successive editions. This made it possible to record 16,608 observations using the photogrammetric method: 29 features describing spatially body posture. Results. Four features influencing the value of features describing the posture were selected for the analysis like an angle of trunk flexion and extension in the sagittal plane, an angle of flexion to the left and right in the frontal plane on selected sagittal and frontal features. Conclusions. (1) The influence of trunk flexion and extension angles in the sagittal plane and left and right flexion in the frontal oplane on the spine features is multidirectional and differential. (2) Spine characteristics are significantly and positively affected in particular by the value of the trunk extension angle in the sagittal plane and the value of the left flexion angle in the frontal plane, and negatively the value of the flexion angle in the sagittal plane. (3) None of the examined angles affect the characteristics of the pelvis.